2021
DOI: 10.1051/shsconf/202110706006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the methods of assessing the influence of external factors on the strengths and weaknesses of the enterprise

Abstract: In the article considered the issues of constructing a classic SWOT analysis matrix, forming a list of key factors of the external and internal environment to assess the degree of their impact on the activities of real enterprises of Ukraine, improving the method of conducting SWOT analysis through the use of scientifically based scales and indicators. The thesis justified that SWOT analysis and other classic strategic management tools are conceptually described, and their use causes many approaches to their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The proposed strategy of economic development is based on the SO-strategies, which was determined by the constructed SWOT-matrix. Some authors prioritized the factors of SWOT analysis and noted that the development strategy is based on them (Lozovik et al, 2021). The developed economic development strategy is based on the definition of the environment and conditions for the implementation of the strategy at the micro-, meso-and macroeconomic level.…”
Section: Discussion and Discussion Of The Results Of The Studymentioning
confidence: 99%
“…The proposed strategy of economic development is based on the SO-strategies, which was determined by the constructed SWOT-matrix. Some authors prioritized the factors of SWOT analysis and noted that the development strategy is based on them (Lozovik et al, 2021). The developed economic development strategy is based on the definition of the environment and conditions for the implementation of the strategy at the micro-, meso-and macroeconomic level.…”
Section: Discussion and Discussion Of The Results Of The Studymentioning
confidence: 99%
“…In the article by Trenerry, et al [15], an important point is indicated -the presence of multi level influence of external and internal factors on the digital economy. The work by Lozovik, et al [16] is devoted to the improvement of methods for assessing the influence of external factors and the formation of their groups, that is, the need to manage their influence is pointed out. KuangHua, et al [17] indicated that the determination of the key factors influencing certain areas of the digital economy should be performed only by using mathematical methods.…”
mentioning
confidence: 99%